Cytotoxicity of peracetic acid: evaluation of effects on metabolism, structure and cell death - Viola, K. S. [UNESP]; Rodrigues, E. M. [UNESP]; Tanomaru-Filho, M. [UNESP]; Carlos, I. Z. [UNESP]; Ramos, S. G.; Guerreiro-Tanomaru, J. M. [UNESP]; Faria, G. [UNESP] (Wiley, 2018)
Aim: To evaluate the cytotoxicity and the mechanism of cell aggression of peracetic acid (PA) in comparison with sodium hypochlorite (NaOCl). Methodology: L929 fibroblasts were exposed to 1% PA and 2.5% NaOCl, at several dilutions for 10 min. The following parameters were evaluated: cell metabolism by methylthiazol tetrazolium assay, external morphology by scanning electron microscopy, ultrastructure by transmission electron microscopy, the cytoskeleton by means of actin and α-tubulin labelling, and the type of cell death by flow cytometry (apoptosis/necrosis). The data were analysed by two-way anova and the Bonferroni post-test (α = 0.05). Results: The PA group had lower cell viability and a higher percentage of necrotic cells than the NaOCl group (P < 0.05). Both solutions diminished cell metabolism, led to destructuring of the cytoskeleton, created changes in the external morphology, resulted in the accumulation of proteins in the rough endoplasmic reticulum and induced cell death predominantly by necrosis. However, these changes were observed in lower doses of PA when compared with NaOCl. Conclusions: Although they had the same mechanism of cytotoxicity, 1% PA had greater cytotoxic potential than 2.5% NaOCl.
Keywords: cytotoxicity; endodontics; fibroblasts; peracetic acid; sodium hypochlorite